User Experience Prototype for Simple and Intuitive Transanal Irrigation - Karlsson, Fredrik (My University, 2021)
For most people, the act of going to the bathroom is not a big deal. However, for people with bowel disfunction, this act can be thought of differently. Bowel disfunction can happen to anyone as a result of an illness or an accident. Some people with bowel disfunction use transanal irrigation which is a procedure where the user instill water into the bowel to loos en the feces and to stimulate bowel movement. Using transanal irrigation allows the user to choose when and where to empty the bowel. This enables the user to regain control over a part of their life. The current smart transanal irrigation product which is being redesigned in the thesis have some usability issues and the review functionality is not widely adopted which would be beneficial to solve. The aim of the thesis is to create prototypes which provides a more intuitive and positive user experience when performing transanal irrigation. Firstly, the project started with three para-llel phases to create understandings: interviews, digital prototype tests and physical prototype tests. Secondly, the insights from the first three phases have been used to create requirements, focus areas and guidelines to influence the concept decision and the next designs. Lastly, a final prototype was designed to be used for further testing. The final prototype uses a combination of physical buttons which ensures that the user feels in control when performing the treatment and a resistive touchscreen which enables an easy way to interact with interface. The experience of reviewing the treatment has been simplified and put in the device, from previously being in an app. This enables the user to faster and more conveniently make the review. The interface also includes information boxes and more informative error messages which lets new users learn about the treatment. This project is thought of as one iteration of the development and thus multiple more needs to be made to cover more areas. The result of this thesis helps the development of the unit to take a step in the right direction in terms of further considering the needs of the users.
Keywords: Interaction design, Prototyping, Human-centered design, MedTech, eHealth, User testing, User Interface